Analysis of Code Switching Used by Maudy Ayunda in the Bicara Cinta Podcast - Sari, Ida Juvita; Ajeng, Galuh Dwi; Maximilian, Aksendro (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study investigates the use of code-switching as a bilingual communication strategy in the Bicara Cinta podcast, focusing on Maudy Ayunda’s Indonesian–English language use. Positioned within applied linguistics and digital discourse studies, the research aims to identify the types of code-switching employed and to understand their communicative relevance in a public media context. Using a qualitative design with a content analysis approach, naturally occurring utterances from the podcast were examined. The analysis reveals 73 instances of code-switching, consisting of 16 inter-sentential switches, 42 intra-sentential switches, and 15 tag switches. The predominance of intra-sentential switching reflects a high level of bilingual proficiency and flexible linguistic negotiation. These findings provide insights into bilingual practices in Indonesian digital media and offer pedagogical implications for English education, particularly in promoting sociolinguistic awareness and authentic exposure to bilingual discourse.